Bead-rod-spring models in random flows - Plan, ELCVM; Ali, A; Vincenzi, D (American Physical Society, 2016)
Bead-rod-spring models are the foundation of the kinetic theory of polymer solutions. We derive the diffusion equation for the probability density function of the configuration of a general bead-rod-spring model in short-correlated Gaussian random flows. Under isotropic conditions, we solve this equation analytically for the elastic rhombus model introduced by Curtiss, Bird, and Hassager [Adv. Chem. Phys. 35, 31 (1976)].